Biotechnology 1 - Stonebarger, Bill; Hawkhill Associates Inc. (Madison, WI : Hawkhill Associates Inc., 2002)
Cloning: how and why takes students inside a modern mammal cloning laboratory to see how it is done. Stem cells goes to James Thomson's laboratory at the University of Wisconsin where stem cells
Title from title screen
Videography, Jane Denny...[et al.] ; music, Michael Stonebarger
Narrator: Bill Stonebarger
DVD format
Keywords: Biotechnology; Cloning; Stem cells -- Transplantation; Genetic engineering